Manual Therapy Research Methods in Animal Models, Focusing on Soft Tissues - Bove, Geoffrey M.; Chapelle, Susan L.; Barrigar, Matthew J. S.; Barbe, Mary F. (Frontiers in Integrative Neuroscience, 2022)
Manual therapies have been practiced for centuries, yet little research has been performed to understand their efficacy and almost no animal research has been performed to inform mechanisms of action. The methods of manual therapy practice are quite varied and present a challenge for scientists to model the treatments and perform research using rodents. In this perspective we present a descriptive analysis of the complexity of the treatments, highlighting the role of tissue mechanics and physics. With these complexities in mind, we compare using manual therapy as clinically practiced, to attempts to develop machinery to model or mimic manual therapy. We propose that because of the complexities of manual therapy as practiced, having therapists perform the treatments on research animals just as they would on humans is the most scientific approach. Our results using this approach have supported its practicality.